2009
DOI: 10.1183/09031936.00022908
|View full text |Cite
|
Sign up to set email alerts
|

House dust mite induces direct airway inflammation in vivo: implications for future disease therapy?

Abstract: House dust mite (HDM) is the major source of allergen in house dust and is strongly associated with the development of asthma. HDM can evoke a direct, nonallergic inflammatory reaction in vitro. We aimed to determine whether this apparent nonallergic, inflammatory response can be observed in a more complex in vivo setting.Vehicle, Alum TM or HDM (Dermatophagoides pteronyssinus 5 mg, i.p. with Alum) sensitisedBrown-Norway rats were challenged intratracheally with vehicle (saline), HDM (Der p 10 mg) or heat-inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 42 publications
(61 reference statements)
7
34
0
Order By: Relevance
“…Furthermore, the in vitro effects could not be prevented by heat inactivation and could not be mimicked by LPS administration. In line with our observations, De Alba et al have shown that the Greer extract was still able to induce manifestations of asthma upon heat inactivation in a rat model 26. Our data show for the first time that serine/cysteine proteases and chitinases in HDM extracts are not critically required for disruption of epithelial barrier function in vitro and innate immune responses in vivo, and hence subsequent allergic sensitisation and eosinophilic airway inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the in vitro effects could not be prevented by heat inactivation and could not be mimicked by LPS administration. In line with our observations, De Alba et al have shown that the Greer extract was still able to induce manifestations of asthma upon heat inactivation in a rat model 26. Our data show for the first time that serine/cysteine proteases and chitinases in HDM extracts are not critically required for disruption of epithelial barrier function in vitro and innate immune responses in vivo, and hence subsequent allergic sensitisation and eosinophilic airway inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…We used a clinically relevant murine model of asthma induced by repeated exposure to HDM (D. pteronyssinus), a common aeroallergen that is an environmental trigger and risk factor for the development of persistent asthma (14,24). HDM is a complex mixture of proteins and lipopolysaccharide, which can induce airway inflammation via allergic and nonallergic mechanisms (25)(26)(27). Furthermore, the mechanism of HDM-induced asthma, involves Toll-like receptor 4 signaling in airway epithelial cells, with resultant activation of innate and adaptive immune responses (28).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we assessed sensitisation to house dust mites, cat fur and grass pollen, three common allergens with a high prevalence of sensitisation in our community. House dust mite (D. pteronyssinus) exposure is linked to increased cellular inflammation, including eosinophilia and an increased responsiveness or sensitivity to methacholine [7,8], and plays an important role in the initiation of allergic airway inflammation [9]. In this study, elevated IgE antibodies to D. pteronyssinus did not correlate with the occurrence of adverse respiratory events.…”
Section: Discussionmentioning
confidence: 64%